(untitled) (Avocetta, 2017)
The monitoring of the Golden Eagle Aquila chrysaetos population in Friuli Venezia Giulia was carried out at a regional scale only in the mid 90s (Genero & Caldana 1997). Since then, regional data was never updated; however, since 1999 a systematic monitoring of the species has been carried out by the “Parco Naturale delle Dolomiti Friulane” (PNDF), covering almost the whole mountainous sector of the Western Friuli (Borgo 2009a), a total area of 690 km2. The update of the situation and knowledge level are therefore very heterogeneous, as the PNDF acts as a sample study area for the monitoring of this species at a regional level. The PNDF performs this long-term monitoring of the Golden Eagle because some population parameters and diet composition have been identified as indicators of factors and dynamics affecting the ecosystem (fanALP 2010). Observations, carried out through established methodologies, has been focused on the monitoring of pairs, nests localization and determination of the typical parameters used to study the breeding biology of the species. Data collection on the diet was carried out by observing prey transport to the nest or, in rare cases, by collecting prey remains at the end of the breeding season (Borgo 2009a). The pair density has been measured using the Nearest Neighbour Distance method (NNDM).